Splicing together sister chromatids. (29th September 2014) - Valcárcel, Juan; Malumbres, Marcos
<x xml:space="preserve">Abstract</x> Splicing of pre‐mRNAs is a necessary step for expression of the majority of genes in higher eukaryotes, and its regulation through alternative splice site selection shapes their proteomes. Defects in multiple splicing factors result in aberrant mitotic progression, although the molecular basis for this observation has remained elusive. Recent papers in The EMBO Journal and EMBO Reports reveal that expression of sororin, a critical regulator that stabilizes cohesin rings in sister chromatids, is exquisitely sensitive to defects in the splicing machinery, thus explaining the striking link between spliceosome function and chromosome segregation.